2021
DOI: 10.1111/ene.14786
|View full text |Cite
|
Sign up to set email alerts
|

Association between neuropathy and B‐vitamins: A systematic review and meta‐analysis

Abstract: Background Peripheral neuropathy (PN) is common in patients with diseases that are in turn associated with deficiency of the B‐vitamins, and vitamin treatment has shown mixed results. Methods This systematic review and meta‐analysis studied the association between PN/pain and B‐vitamin biomarkers and investigated whether vitamin treatment can ameliorate the symptoms. PubMed and Web of Science were searched according to the study protocol. Results A total of 46 observational and seven interventional studies wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
16
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 70 publications
4
16
0
3
Order By: Relevance
“…Alteration in the mentioned reactions due to both genetic defect and VitB12 deficiency trigger serious diseases as methionine is required for the synthesis of S-adenosylmethionine (a universal methyl donor involved in a wide range of functions concerning DNA, RNA, proteins, and lipids and hormones), and the conversion of L-methylmalonyl-CoA to succinyl-CoA is essential in fat and protein metabolism. In addition, the absence of VitB12 determines the accumulation of methylmalonic acid and homocysteine that at high levels are toxic [2,6,7]. Both the fact that the organism cannot synthesize the vitamin and the crucial importance in metabolism establish its pivotal role in life.…”
Section: Introductionmentioning
confidence: 99%
“…Alteration in the mentioned reactions due to both genetic defect and VitB12 deficiency trigger serious diseases as methionine is required for the synthesis of S-adenosylmethionine (a universal methyl donor involved in a wide range of functions concerning DNA, RNA, proteins, and lipids and hormones), and the conversion of L-methylmalonyl-CoA to succinyl-CoA is essential in fat and protein metabolism. In addition, the absence of VitB12 determines the accumulation of methylmalonic acid and homocysteine that at high levels are toxic [2,6,7]. Both the fact that the organism cannot synthesize the vitamin and the crucial importance in metabolism establish its pivotal role in life.…”
Section: Introductionmentioning
confidence: 99%
“…A complete autoimmune antibody panel and endocrinology studies should be performed to rule out conditions such as thyroid, pituitary, and adrenal disorders, myasthenia gravis, and celiac disease. Vitamin studies can also be performed to rule out other causes of neuropathy [ 5 ]. If all of these investigations prove to be benign, it may be appropriate to consult with a geneticist for a whole-genome sequencing study including mitochondrial disorders [ 6 ] and Ashkenazi Jewish-related conditions [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The study reported an association with different types of neuropathies among which diabetes was most significant. It recommended screening for vitamin B12 deficiency for patients at risk for neuropathy and those with neuropathy [ 10 ].…”
Section: Discussionmentioning
confidence: 99%